Self-Efficacy with the Quality of Life of Pulmonary Tb Patients - Usastiawaty C.A.S Isnainy; Ridwan Ridwan; Rias Tusianah; M. Arifki Zainaro; Albet Maydiyantoro; Tubagus Ali Rachman Puja Kesuma (Indian Journal of Forensic Medicine & Toxicology, 2022)
Aim: It is known that the relationship between self-efficacy and quality of life in patients with pulmonary tuberculosisat Pertamina Bintang Amin Hospital in Bandar Lampung 2020.Methods: This type of research was quantitative with a cross sectional approach. The population was all pulmonary TB patients at the Pertamina Bintang Amin Hospital Bandar Lampung, with a sample size of 62 people. Data analysis in this study used the chi-square test.Results: The results of the univariate analysis showed that most of the respondents’ self-efficacy was in poor condition, namely as many as 33 people (53.2%). Most of the respondents’ quality of life was in the medium category, namely 27 people (43.5%). The results of the bivariate analysis showed that the p-value = 0.001). 1) demographic factors such as the type of education level are an indicator of the potential vulnerability of pulmonary TB infection, 2) Most of the respondents’ self-efficacy was in poor condition, namely 33 people (53.2%). Most of the respondents’ quality of life was in the medium category, namely 27 people (43.5%), and 3) there was a relationship between self-efficacy and the quality of life of patients with pulmonary tuberculosis.